Aerosol vaccination of chicken pullets with irradiated avian pathogenic Escherichia coli induces a local immunostimulatory effect - Bagheri, Sina; Mitra, Taniya; Paudel, Surya; Abdelhamid, Mohamed Kamal; Könnyü, Simon; Wijewardana, Viskam; Kangethe, Richard Thiga; Cattoli, Giovanni; Lyrakis, Manolis; Hess, Claudia; Hess, Michael; Liebhart, Dieter (Frontiers in Immunology, 2023)
The present study investigated the expression of cytokines and cellular changes in chickens following vaccination with irradiated avian pathogenic Escherichia coli (APEC) and/or challenge. Four groups of 11-week-old pullets, each consisting of 16 birds were kept separately in isolators before they were sham inoculated (N), challenged only (C), vaccinated (V) or vaccinated and challenged (V+C). Vaccination was performed using irradiated APEC applied via aerosol. For challenge, the homologous strain was administered intratracheally. Birds were sacrificed on 3, 7, 14 and 21 days post challenge (dpc) to examine lesions, organ to body weight ratios and bacterial colonization. Lung and spleen were sampled for investigating gene expression of cytokines mediating inflammation by RT-qPCR and changes in the phenotype of subsets of mononuclear cells by flow cytometry. After re-stimulation of immune cells by co-cultivation with the pathogen, APEC-specific IFN-γ producing cells were determined. Challenged only birds showed more severe pathological and histopathological lesions, a higher probability of bacterial re-isolation and higher organ to body weight ratios compared to vaccinated and challenged birds. In the lung, an upregulation of IL-1β and IL-6 following vaccination and/or challenge at 3 dpc was observed, whereas in the spleen IL-1β was elevated. Changes were observed in macrophages and TCR-γδ+ cells within 7 dpc in spleen and lung of challenged birds. Furthermore, an increase of CD4+ cells in spleen and a rise of Bu-1+ cells in lung were present in vaccinated and challenged birds at 3 dpc. APEC re-stimulated lung and spleen mononuclear cells from only challenged pullets, showed a significant increase of IFN-γ+CD8α+ and IFN-γ+TCR-γδ+ cells. Vaccinated and challenged chickens responded with a significant increase of IFN-γ+CD8α+ T cells in the lung and IFN-γ+TCR-γδ+ cells in the spleen. Re-stimulation of lung mononuclear cells from vaccinated birds resulted in a significant increase of both IFN-γ+CD8α+ and IFN-γ+TCR-γδ+ cells. In conclusion, vaccination with irradiated APEC caused enhanced pro-inflammatory response as well as the production of APEC-specific IFN-γ-producing γδ and CD8α T cells, which underlines the immunostimulatory effect of the vaccine in the lung. Hence, our study provides insights into the underlying immune mechanisms that account for the defense against APEC.